Estimating effects of constraints on food security in Malawi: policy lessons from regressions quantiles - Matchaya, Greenwell C.; Chilonda, Pius (2012)
This paper examines food insecurity in Malawi. Conceiving food security as tridimensional, it is shown using Quantile, logistic, and OLS regressions that food security in Malawi is a function of both supply and demand factors. Specifically, food security as proxied by dietary diversity, reported food security, and food end time is a function of farm level production as proxied by farm level incomes. It is also a function of credit accessed, age and sex of a household head, while access to the markets, extension information, radio ownership, assets such as housing and adoption of a cash crop (tobacco). Education and consumer worker ratio are also important signifying the role that knowledge and labour play in deciding household level food security. The results also show that the impact of the regressors on food security depends on the level of food security in question such that in general factors with a positive effect on food security have a greater impact on food insecure households than on households that are better off. Given the preponderance of evidence in this paper it appears that policies that seek to enhance market access, improve market opportunities, enhance extension services, enhance informal education, encourage cash cropping, and support household level consolidation of assets would be useful for enhancing household level food security.